The Effect of Financial Literacy and Capital Management on MSME Performance - Lubis, Kartika Sari; Irawati, Lelisa (Asean International Journal of Business, 2022)
Purpose–This study aims to determine whether there is an effect of financial literacy, financial management, and capital on the performance of UMKM at Ida Martunas LKM for the 2017-2020 period. Method– The data analysis method used in this study is a quantitative descriptive method and a simple linear regression test analysis model, the test is carried out using the classical assumption of normality and linearity as well as the hypothesis being tested using the coefficient of determination (R2) , simultaneous test (F test) and partial test (t test) with data processing using the SPSS Statistics 22 program. Findings–The results showed that the coefficient of determination test (R2) obtained a result of 0.984 or 98.4% indicating that the variables of financial literacy, financial management, and capital were able to explain the variations that occur in the performance of MFI Ida Martunas, while the remaining 1.6% is explained by other variables not examined. The results of the partial study of financial literacy and financial management have no and no significant effect on the performance of MSMEs, while capital has a negative and significant effect on the performance of MSMEs at Ida Martunas LKM. Meanwhile, the results of simultaneous testing of financial literacy, financial management, and capital have a significant and significant effect on the performance of MSMEs at Ida Martunas LKM.